The Effect of The Use of Genially-Based Interactive Learning Media on Interest in Learning Mathematics in Elementary School Students - Kholidah, Ika; Dewi, Sri Enggar kencana; Dewi, Tri Ratna (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2026)
This research aims to determine how students' interest in learning mathematics changes before and after using interactive learning media based on Genially. Additionally, it also examines how the use of this media impacts fifth-grade students at SD Negeri 03 Gumawang. The research method used is experimental quantitative and employs a one-group Pretest-Posttest design. Systematic sampling was used to determine the research subjects, which consisted of 30 students. The tools used to collect data include observation, questionnaires, and interviews. Then, to determine the difference between before and after the treatment, a series of statistical tests were used, including normality, validity, and reliability tests, as well as the paired sample t-test. The results of the data processing show that after the use of Genially media, students' interest in learning antematika increased. The average student score increased from 46.41 before the treatment to 53.65 after the treatment. Furthermore, it can be concluded that the use of Genially-based learning media has a significant impact on students' interest in learning. The results of the statistical test show a significance value of 0.000, which is below the 0.05 threshold.